Reduced UCP-1 content in in vitro differentiated beige/brite adipocytes derived from preadipocytes of human subcutaneous white adipose tissues in obesity. - Andrew L Carey; Camilla Vorlander; Medini Reddy-Luthmoodoo; Alaina K Natoli; Melissa F Formosa; David A Bertovic; Mitchell J Anderson; Stephen J Duffy; Bronwyn A Kingwell (PLoS ONE, 2014)
Brown adipose tissue (BAT) is a potential therapeutic target to reverse obesity. The purpose of this study was to determine whether primary precursor cells isolated from human adult subcutaneous white adipose tissue (WAT) can be induced to differentiate in-vitro into adipocytes that express key markers of brown or beige adipose, and whether the expression level of such markers differs between lean and obese young adult males.Adipogenic precursor cells were isolated from lean and obese individuals from subcutaneous abdominal WAT biopsies. Cells were grown to confluence, differentiated for 2.5 weeks then harvested for measurement of gene expression and UCP1 protein.There was no difference between groups with respect to differentiation into adipocytes, as indicated by oil red-O staining, rates of lipolysis, and expression of adipogenic genes (FABP4, PPARG). WAT genes (HOXC9, RB1) were expressed equally in the two groups. Post differentiation, the beige adipose specific genes CITED1 and CD137 were significantly increased in both groups, but classic BAT markers ZIC1 and LHX8 decreased significantly. Cell lines from both groups also equally increased post-differentiation expression of the thermogenic-responsive gene PPARGC1A (PGC-1α). UCP1 gene expression was undetectable prior to differentiation, however after differentiation both gene expression and protein content were increased in both groups and were significantly greater in cultures from lean compared with obese individuals (p<0.05).Human subcutaneous WAT cells can be induced to attain BAT characteristics, but this capacity is reduced in WAT cells from obese individuals.